Feedlot Performance of Sudan Baggara Bulls Fed Pelleted and Unpelleted Baggase Based Diets - El Khidir, Omer A.; Babiker, zeldin Adam; Amir, M.S. Mukhtar (Pakistan Journal of Nutrition, 2009)
The present study was conducted to evaluate the effect of physical form of the diet, use of sugarcane baggase as basal roughage in complete diet system and the joint effect of dietary energy and protein on Sudan Baggara bulls performance. Two experimental baggase based diets(BBD) were used in feeding 18 entire Sudan Baggara bulls (1.5 year old and at average weight 200±7.56 kg). These bulls were randomly divided into 2 treatment groups of nine animals each. Further, each group blocked into three subgroups of three animals. Following an adaptation period of 3 weeks, 2 experimental diets of the same ingredients, metabolizable energy and CP content (but differed physically were diet A is unpelleted and diet B is pelleted were used. The experiment in this study showed variable results between the two treatment groups due to the difference in the physical form of the diets, but no significant differences (p>0.05) between the two treatment groups in many parameters, these are, the Average Daily Gain (ADG), daily DMI, total DMI, feed intake as percent of the body weight and, ME intake and the period of feeding. Feed Conversion Ratio (FCR) was significantly (p